Sustaining the military enterprise an architecture for a lean transformation - Mathaisel, Dennis F. X. (Series on resource management, 2008)
Providing both engineering and management views on the subject, this title focuses on the tools that management, product development, and operational support teams must consider in the design, development, operation, and improvement of products that are cost-effective in various phases of the life cycle.